Ethnicity and Inclusion: Religion, Race, and Whiteness in Constructions of Jewish and Christian Identities - Horrell, David G. (Wm. B. Eerdmans Publishing Co., 2020)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- Foreword by Judith M. Lieu -- Acknowledgments -- Abbreviations -- Introduction -- Contexts of Research -- 1. A Persistent Structural Dichotomy: Jewish Ethnic Particularism and Christian Inclusivism -- 1.1 Ferdinand Christian Baur and the Making of Modern New Testament Scholarship -- 1.2 E. P. Sanders and a New Perspective on Judaism -- 1.3 Social-Scientific Perspectives on Ethnicity and Identity -- 1.4 Conclusions -- 2. Ethnicity, Race, and Ancient Jewish and Christian Identities: Themes in Recent Research -- 2.1 Ethnicity and Race in Antiquity: Jews/Judeans and Greeks -- 2.2 Ethnicity and Race in Early Christian Discourse and Identity -- 2.3 Conclusions -- 3. Ethnicity, Race, and Religion in Social-Scientific Perspective -- 3.1 Ethnicity and Race in History and Theory -- 3.2 The Language of Race -- 3.3 Religion and Ethnicity -- 3.4 Conclusions -- Comparisons of Jewish and Early Christian Perspectives -- 4. Shared Descent: Ancestry, Kinship, Marriage, and Family -- 4.1 Stories of Ancestors: Appeals to Genealogy and Descent -- 4.2 Kinship Relations: A Community of Brothers and Sisters -- 4.3 Marriage Rules: Endogamy as Norm -- 4.4 The Holiness of Children and the Passing on of Christian Identity -- 4.5 Conclusions -- 5. A Common Way of Life: Culture, Practice, and the Socialization of Children -- 5.1 Adhering to a Way of Life as Definitive for Jewish and Christian Identity -- 5.1.1 Way of Life and Jewish Identity -- 5.1.2 Way of Life and Christian Identity -- 5.2 The Socialization of Children into a Way of Life -- 5.2.1 Training Children in the Jewish Way of Life -- 5.2.2 Children and the Christian Way of Life -- 5.3 Displaying a Way of Life through Practice -- 5.3.1 Jewish Practices as Markers of Identity: Circumcision, Food, and Sabbath.